Isolation and expansion of pure and functional γδ T cells - Verkerk, Tamara; Pappot, Anouk T.; Jorritsma, Tineke; King, Lisa A.; Duurland, Mariël C.; Spaapen, Robbert M.; van Ham, S. Marieke (Frontiers in Immunology, 2024)
γδ T cells are important components of the immune system due to their ability to elicit a fast and strong response against infected and transformed cells. Because they can specifically and effectively kill target cells in an MHC independent fashion, there is great interest to utilize these cells in anti-tumor therapies where antigen presentation may be hampered. Since only a small fraction of T cells in the blood or tumor tissue are γδ T cells, they require extensive expansion to allow for fundamental, preclinical and ex vivo research. Although expansion protocols can be successful, most are based on depletion of other cell types rather than γδ T cell specific isolation, resulting in unpredictable purity of the isolated fraction. Moreover, the primary focus only lies with expansion of Vδ2+ T cells, while Vδ1+ T cells likewise have anti-tumor potential. Here, we investigated whether γδ T cells directly isolated from blood could be efficiently expanded while maintaining function. γδ T cell subsets were isolated using MACS separation, followed by FACS sorting, yielding >99% pure γδ T cells. Isolated Vδ1+ and Vδ2+ T cells could effectively expand immediately after isolation or upon freeze/thawing and reached expansion ratios between 200 to 2000-fold starting from varying numbers using cytokine supported feeder stimulations. MACS/FACS isolated and PHA stimulated  T cells expanded as good as immobilized antibody mediated stimulated cells in PBMCs, but delivered purer cells. After expansion, potential effector functions of γδ T cells were demonstrated by IFN-, TNF- and granzyme B production upon PMA/ionomycin stimulation and effective killing capacity of multiple tumor cell lines was confirmed in killing assays. In conclusion, pure γδ T cells can productively be expanded while maintaining their anti-tumor effector functions against tumor cells. Moreover, γδ T cells could be expanded from low starting numbers suggesting that this protocol may even allow for expansion of cells extracted from tumor biopsies.